Ozonolysis in flow using capillary reactors - Roydhouse, Mark D.; Ghaini, Aras; Constantinou, Achilleas; Cantú-Pérez, Alberto; Motherwell, William B.; Gavriilidis, Asterios (My University, 2011)
Reactions of n-decene with ozone and subsequent quenching of the formed ozonides were carried out under flow conditions using the standard Vapourtec flow system equipped with a cooled flow cell. The reactions were performed continuously and in the annular flow regime within the circular cross-section channels. Typical flow rates were 0.25-1 mL min-1 for liquid and 25-100 mL min-1 for gas, reactor volumes were 0.07-10 mL formed of 1 mm ID PFA tubing. The reaction temperature was -10 °C. The flow was not always smooth, while waves in the liquid film and droplets in the gas core were observed. Liquid residence times were found to be independent of gas flow rates and increasing with decreasing liquid flow rates. Substrate residence times in the ozonolysis reactor ranged between 1 and 80 s, and complete conversion could be achieved at ∼1 s residence time. Two common reductants, triethylphosphite and triphenylphosphine, were examined as to their suitability under flow conditions. Triphenylphosphine achieved faster reduction of the intermediate ozonides, resulting in a greater than 10:1 selectivity for the aldehyde over the corresponding acid. The cooling system provided a safe and efficient control of the highly exothermic reaction system. The configuration of the system allowed the production of chemically significant amounts (1.8 g h-1 at 1.3 ozone equivalents), with minimal amounts of ozonides present at any time.
Keywords: Redox reactions; Liquids; Organic reactions; Chromatography; Colloids